1995
DOI: 10.20506/rst.14.3.883
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of the tick Amblyomma variegatum in the Caribbean

Abstract: The tropical bont tick, Amblyomma variegatum, is an African tick species which infests livestock and wildlife. It was probably introduced in the central eastern islands of the Caribbean during the 18th or 19th century, with cattle shipped from Senegal. In Africa and the Caribbean, this tick is a vector of heartwater (a rickettsial disease of ruminants) and is associated with acute dermatophilosis (a bacterial skin disease of animals). Until 1948, only Guadeloupe and the neighbouring islands of Marie Galante an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 21 publications
0
49
0
2
Order By: Relevance
“…While the disease has only become established on the islands of Guadeloupe, Antigua and Marie-Galante (36,37), the tick vector has spread to 14 islands as a result of inter-island trade in tick-infested livestock and the transport of larvae and nymphs by the African cattle egret (Bubulcus ibis) (38). Cattle egrets migrate as far as the American mainland so both A. variegatum and E. ruminantium could continue to spread.…”
Section: Epidemiology In the New Worldmentioning
confidence: 99%
“…While the disease has only become established on the islands of Guadeloupe, Antigua and Marie-Galante (36,37), the tick vector has spread to 14 islands as a result of inter-island trade in tick-infested livestock and the transport of larvae and nymphs by the African cattle egret (Bubulcus ibis) (38). Cattle egrets migrate as far as the American mainland so both A. variegatum and E. ruminantium could continue to spread.…”
Section: Epidemiology In the New Worldmentioning
confidence: 99%
“…19 Over the past 50 years, it has propagated and invaded more than 15 islands, including Martinique, Dominica, St. Lucia, St. Vincent, Barbados, and Puerto Rico. 19 In the Caribbean, cattle and goats are the main hosts of adults, whereas immature forms may parasitize a large variety of hosts, including birds.…”
Section: Amblyomma Variegatummentioning
confidence: 99%
“…19 Over the past 50 years, it has propagated and invaded more than 15 islands, including Martinique, Dominica, St. Lucia, St. Vincent, Barbados, and Puerto Rico. 19 In the Caribbean, cattle and goats are the main hosts of adults, whereas immature forms may parasitize a large variety of hosts, including birds. Although livestock movements have been implicated in the explanation of the propagation of the tick in the West Indies, Barré and others have suggested that bird migration may play a role in carrying ticks.…”
Section: Amblyomma Variegatummentioning
confidence: 99%
See 2 more Smart Citations